PENERAPAN STRATEGI PEMBELAJARAN AKTIF EACH ONE TEACH ONE DAPAT MENINGKATKAN HASIL BELAJAR MATA PELAJARAN IPS KOMPETENSI DASAR MENGIDENTIFIKASI BENTUK PASAR DALAM KEGIATAN EKONOMI MASYARAKAT PADA SISWA KELAS VIII-A DI SMP NEGERI 1 KENDIT - Rahman Ardiansah; Nursalam Nursalam (STKIP PGRI SITUBONDO, 2018)
Based on observation smp country 1 kendit and interview with subject teacher ips class economy VIII especially class VIII-A. class stipulating VIIIC as this watchfulness subject is provided by several things among others: (1) student more co-operative membanding with class student other, (2) student passiveer in course of study and (3) heterogeneous student ability. in general, teacher in course of study uses lecture method and never divide student into groups learn. based on background on, so problem formulation as follows: 1) how does mobile study strategy applications each one teach one can increase activity learn subject IPS competence base identify market form in society economic activity in class student VIII-A at SMP country 1 Kendit Situbondo? , 2) how does mobile study strategy applications each one teach one can increase result learn subject IPS competence base identify market form in society economic activity in class VIII-A at SMP country 1 Kendit Situbondo?. Watchfulness design in this watchfulness ptk with berkolaborasi with teacher that is done 2 cycles. in ptk there 4 stages that is planning, action, observation and reflection. primary data by using repetition test and observation with at checklist, and secondary data with interview. researcher uses target value necessity or KKM (criteria ketuntasan minimal) determine successful criteria to analyzes data. Based on watchfulness result at chapter iv inferential as follows: 1) mobile study strategy applications each one teach one can increase activity learn from 67% my cycle be 93% cycle II subject IPS competence base identify market form in society economic activity in class student VIII-A at SMP country 1 Kendit Situbondo, 2) mobile study strategy applications each one teach one can increase result learn from 65% my cycle be 92% cycle II subject ips competence base identify market form in society economic activity in class student VIII-A at SMP country 1 Kendit Situbondo